UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK SISWA DI SD NEGERI 11 KEPAHIANG - Ikaddmi, Ikaddmi; Nurjannah, Nurjannah (Yayasan Literasi Kita Indonesia, 2024)
This study discusses the efforts of Islamic religious education teachers in fostering the morals of students at SD Negeri 11 Kepahiang. The purpose of this study was to determine the efforts of Islamic religious education teachers in fostering the morals of students at SD Negeri 11 Kepahiang. This research method is a qualitative method, namely by conducting an observation, interview, and documentation approach. From the results of this study, it can be concluded that Islamic religious education teachers at SD Negeri 11 Kepahiang carry out coaching through moral coaching that can be formed through habits that are carried out in a small history and take place continuously. Moral coaching through role models, good morals cannot only be formed with lessons, intrusions and prohibitions and effective moral coaching can be done by paying attention to the psychological factors of the targets to be fostered, from the results of the study, SD Negeri 11 Kepahiang is categorized as quite good, this can be seen from the coaching process carried out by Islamic Religious Education Teachers.